Parental Raising Style, Personality and self-regard among School Adolescents - Gajurel, Mahesh Kumar (Journal of Balkumari College, 2022)
100 adolescents (50 boy and 50 girls) Subjects were collected from various school in Bharatpur metropolitan city employed with Gerlsma Pecaived Parental Rearing Style (PPRSQ), Kellner Sympton Questionnaire (S.Q.) and Rosenberg Self-Esteem Scale. The results disclase that boys have notably more non acceptance from father ad compared to girls and girls and girls have shown outstandingly better emotional warmth in comparison to boys from father. The boy and girls did not differ significantly on the factors over protection and favoring subjects of PPRSQ for father. No dependable difference was discovered between boys and girls on all the factors of PPRSQ for mother. The differentiation of boys and girls on anxiety, depression, somatic problems, anger hostility and self-esteem pointed out significantly higher anxiety. More somatic problem and increased hostility among boys, and high self-regard in girls. The study highs of the received parental raising style and its effect on personality of adolescents and has educational implications for parents.